Aboriginal Employment: Continuing to Improve in 2012 - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development, 2013)
The employment rate for Aboriginals living off-reserve in Canada continued to improve in 2012. It increased to 56.9%, a rate of two percent (2%) over 2011. This is impressive when compared to the zero growth rate for non-Aboriginals. The participation rate for Aboriginals living off-reserve in Canada also increased. It grew from 64.1% to 65.2%. In addition, the gap between Aboriginals and non-Aboriginals for employment rates and participation rates continued to narrow in 2012. When employment is examined by educational level, there is no meaningful difference between Aboriginals and non-Aboriginals. There is also a clear relationship that increased levels of education are associated with higher employment rates and participation rates. Aboriginal employment in 2012 increased the most in Ontario. It is also the province with the largest Aboriginal as well as non-Aboriginal populations. The sectors in which the largest increases in Aboriginal employment in 2012 occurred were in construction, manufacturing, health care and social assistance and information, culture and recreation.